Depressive symptoms associated with concerns about falling in Parkinson's disease. Issue 10 (21st July 2016) - Franzén, Erika; Conradsson, David; Hagströmer, Maria; Nilsson, Maria H.
Abstract: Background: Concerns about falling, a construct related to fear of falling, is increased in people with Parkinson's disease (PD) and is recognized as a barrier for exercise, negatively affecting health‐related quality of life and participation. Aim: To investigate modifiable factors associated with concerns about falling in elderly with mild‐to‐moderate PD. Methods: Eighty‐nine elderly (39 females, mean age 73 years) with mild‐to‐moderate PD were recruited. Concerns about falling were assessed with the Falls Efficacy Scale‐international, that is, the dependent variable in multiple linear regression analysis. Independent variables included both motor (e.g., objective measures of physical activity and gait) and nonmotor aspects such as depressive symptoms. Results: A model with three significant independent variables explained 33% of the variance in concerns about falling. According to the standardized regression coefficients (β), the strongest contributing factor was depressive symptoms (0.40), followed by balance performance (−0.25), and use of mobility devices (0.24). Conclusions: The findings imply that factors associated with concerns about falling are a multifactorial phenomenon. For its management in elderly with mild‐to‐moderate PD, one should consider depressive symptoms, balance deficits, and mobility devices. Abstract : Concern about falling is increased in people with Parkinson's disease (PD). This study shows that factors associated with concerns about falling are a multifactorial phenomenon. For its management in elderly with mild‐to‐moderate PD, one should consider depressive symptoms, balance deficits, and mobility devices.